Association between Helicobacter pylori infection and the risk of colorectal cancer: A systematic review and meta-analysis. Issue 37 (11th September 2020) - Zuo, Yuling; Jing, Zhao; Bie, Mingjiang; Xu, Chunyan; Hao, Xinyu; Wang, Baoning
Abstract: Background: The existing evidence on the relationship between Helicobacter pylori infection and the risk of colorectal cancer is inconsistent. We conducted a systematic review with a meta-analysis to explore this relationship and to determine whether the relationship varies according to the study characteristics. Methods: We searched the PubMed, OVID, EMBASE database, and the reference lists of pertinent articles published up to October 2019 by 2 researchers independently. Summary odds ratios (OR) with their 95% confidence intervals (CIs) were estimated using a random-effects model. Results: Forty seven studies including 17, 416 cases of colorectal cancer (CRC) and 55, 811 cases of control were included. Overall, H. pylori infection was associated with an increased risk of CRC (OR = 1.70 95% CI 1.64–1.76, I 2 = 97%), although there was significant heterogeneity among the studies. Subgroup analysis revealed that the positive correlation might vary by the design of study conducted. Conclusion: This meta-analysis demonstrates a positive association between H. pylori infection and the risk of colorectal cancer. Abstract : Supplemental Digital Content is available in the text